Getting the best out of college : a professor, a dean, and a student tell you how to maximize your experience - Feaver, Peter; Wasiolek, Sue.; Crossman, Anne. (Berkeley : Ten Speed Press, 2008)
"A guide to optimizing all aspects of the undergraduate college experience, written for students by a professor, a dean, and a recent college graduate"--Provided by publisher.
Includes index.
Keywords: College student orientation -- United States